The Influence Of Work Attitude And Labor Efficiency On Employee Work Productivity At Pt Bank Rakyat Indonesia, Stabat Branch - Divana, Abellia; Waruwu, Ahmad Aswan; Yanti, Eli Delvi (Universitas Dehasen Bengkulu, 2026)
The research analysis aims to determine whether work attitude and labor efficiency have an effect on employee productivity at PT Bank Rakyat Indonesia, Stabat Branch. The data analysis technique used is the associative research method with the help of the SPSS version 25 program. This study uses multiple linear regression analysis. The sample in this study was 45 respondents. Primary data collection used a questionnaire. The results of the study indicate that work attitude partially has a positive and significant effect on employee work productivity at PT Bank Rakyat Indonesia, Stabat Branch. Labor efficiency partially has a positive and significant effect on employee work productivity at PT Bank Rakyat Indonesia, Stabat Branch. Work attitude and labor efficiency simultaneously have a positive and significant effect on employee work productivity at PT Bank Rakyat Indonesia, Stabat Branch.